2010
DOI: 10.1111/j.1478-3231.2010.02223.x
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and reduced risk of hepatocellular carcinoma in diabetic patients with chronic liver disease

Abstract: Our study shows that DM2 is an independent risk factor for HCC and pre-exists to HCC occurrence. In DM2 patients with HCC, metformin therapy is associated with a reduced HCC risk and seems to have a protective effect on HCC development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
213
2
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(239 citation statements)
references
References 55 publications
11
213
2
9
Order By: Relevance
“…Compatible with our findings, is the report that anti-diabetic medications also affect the risk of Hepatocellular Carcinoma [HCC] [7,[20][21][22]. The use of insulin and sulfonylurea was associated with a 161% and 62% increased risk of HCC respectively, while the use of metformin was associated with 50% reduction in the incidence of HCC incidence [23].…”
Section: Discussionsupporting
confidence: 35%
“…Compatible with our findings, is the report that anti-diabetic medications also affect the risk of Hepatocellular Carcinoma [HCC] [7,[20][21][22]. The use of insulin and sulfonylurea was associated with a 161% and 62% increased risk of HCC respectively, while the use of metformin was associated with 50% reduction in the incidence of HCC incidence [23].…”
Section: Discussionsupporting
confidence: 35%
“…Certain antidiabetic agents, especially metformin, were recently reported to reduce the DM-associated HCC risk in patients with chronic hepatitis [6,[31][32][33][34]. One study based on 135 patients who underwent RFA for early HCC also found metformin to be associated with better survival [35].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 143 articles were further excluded because they did not satisfy the inclusion criteria. The remaining 17 studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] complied with the inclusion criteria and were considered for meta-analysis. The main characteristics of the studies included are reported in Table 1.…”
Section: Methodsmentioning
confidence: 99%